PERTUMBUHAN DAN PRODUKSI DUA VARIETAS BAWANG MERAH LOKAL (ALLIUM ASCALONICUM L.) PADA BEBERAPA DOSIS PUPUK NITROGEN ANORGANIK - Safrizal Safrizal; Nazimah Nazimah; Aisah Amini; Nilahayati Nilahayati; Hafifah Hafifah (Lentera : Jurnal Ilmiah Sains, Teknologi, Ekonomi, Sosial, dan Budaya, 2022)
The onions (Allium ascalonicum L.) is one of the horticultural plants that is used as a popular cooking spice and has a layered tuber. Shallots also have benefits in the health sector and have high prospects in the domestic and national market. The high demand for shallots caused by the increase in population so that efforts need to be made to increase productivity. One of the efforts made is the use of varieties that are suitable for the environment and the use of efficient fertilizer doses. This study aims to determine the growth and yield of two local varieties of shallots at various doses of inorganic nitrogen fertilizers and to determine the efficiency of inorganic nitrogen fertilizer doses in the cultivation of several local shallot varieties. The research was carried out at the Experimental Garden of the Faculty of Agriculture and the Laboratory of Agroecotechnology, Faculty of Agriculture, Malikussaleh University from March to May 2021. This study used a 2x4 factorial randomized block design with 3 replications so that there were 24 experimental units and continued with the DMRT test at a level of 5 %. The first factor is the local variety which consists of 2 local varieties, namely V1: Bauji local variety (West Java) and V2: Tajuk local variety (West Java). The second factor is the application of inorganic nitrogen fertilizer with a dose consisting of 4 levels, namely N0: Without Fertilizer N, N1 (13.2 g/plot), N2 (16.8 g/plot) and N3 (20.4 g/plot). Parameters observed were plant height, number of leaves (strands), number of tillers, number of tubers per clump, wet weight of bulbs per clump, wind-dry weight of bulbs per clump, production per plot, and tuber diameter. The Tajuk variety is the best local shallot variety compared to the local Bauji variety and the best dose of inorganic nitrogen fertilizer is at a dose of N1 (13.2 g/plot) and there is an interaction between the number of tubers and the weight of the tubers.